2017
DOI: 10.25201/fer.16.4.86121
|View full text |Cite
|
Sign up to set email alerts
|

Trade Credit or Bank Credit? – Lessons Learned from Hungarian Firms between 2010 and 2015

Abstract: This paper addresses the way in which trade credit was used by Journal of Economic Literature (JEL) codes: G32, C23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Payment terms may have great economic significance, as small and medium-sized enterprises may often take advantage of longer payment deadlines consistently in order to gain access to liquidity, especially if they have no access to other financing channels, such as short-term bank loans. 10 This phenomenon was simulated by Burkart and Ellingsen (2004), on the basis of which Havran et al (2017) empirically demonstrated that on a sample of Hungarian firms a complementary effect could be observed between short-term bank loans and accounts payable in the period of 2010-2015. Moreover, analysing the data of SMEs across 13 European countries over the period of 2003of -2012of , McGuiness et al (2017 found that enterprises with access to trade credit were less likely to face financial distress during the credit crunch of the economic crisis.…”
Section: Studiesmentioning
confidence: 99%
“…Payment terms may have great economic significance, as small and medium-sized enterprises may often take advantage of longer payment deadlines consistently in order to gain access to liquidity, especially if they have no access to other financing channels, such as short-term bank loans. 10 This phenomenon was simulated by Burkart and Ellingsen (2004), on the basis of which Havran et al (2017) empirically demonstrated that on a sample of Hungarian firms a complementary effect could be observed between short-term bank loans and accounts payable in the period of 2010-2015. Moreover, analysing the data of SMEs across 13 European countries over the period of 2003of -2012of , McGuiness et al (2017 found that enterprises with access to trade credit were less likely to face financial distress during the credit crunch of the economic crisis.…”
Section: Studiesmentioning
confidence: 99%